Purinergic and Adenosinergic Signaling in Pancreatobiliary Diseases - Faraoni, Erika Y.; Ju, Cynthia; Robson, Simon C.; Eltzschig, Holger K.; Bailey-Lundberg, Jennifer M. (Frontiers in Physiology, 2022)
Adenosine 5'-triphosphate (ATP), other nucleotides and the nucleoside analogue, adenosine, all have the capacity to generate and modulate cellular signaling pathways. The cellular processes linked to extracellular purinergic signaling are crucial in the initiation, evolution and resolution of inflammation. Injured or dying cells in the pancreatobiliary tract secrete or release ATP, which results in sustained purinergic signaling mediated through ATP type-2 purinergic receptors (P2R). This process can result in chronic inflammation, fibrosis, and tumor development. In contrast, signaling via the extracellular nucleoside derivative adenosine via type-1 purinergic receptors (P1R) is largely anti-inflammatory, promoting healing. Failure to resolve inflammation, as in the context of primary sclerosing cholangitis or chronic pancreatitis, is a risk factor for parenchymal and end-organ scarring with the associated risk of pancreatobiliary malignancies. Emerging immunotherapeutic strategies suggest that targeting purinergic and adenosinergic signaling can impact the growth and invasive properties of cancer cells, potentiate anti-tumor immunity and also block angiogenesis. In this review, we dissect out implications of disordered purinergic responses in scar formation, end-organ injury, and in tumor development. We conclude by addressing promising opportunities for modulation of purinergic/adenosinergic signaling in the prevention and treatment of pancreatobiliary diseases, inclusive of cancer.